PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN CUSTOMER EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN PADA CV. BALI STARS PROMOSINDO CABANG GATOT SUBROTO DENPASAR, BALI - I Nyoman Nesa Nirta Ardiana; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Digital printing is a modern printing technology that utilizes computers to directly print digital images onto physical surfaces, commonly referred to as printers. A study conducted at CV. Bali Stars Promosindo, Gatot Subroto Denpasar, investigates the influence of service quality, product quality, and customer experience on purchasing decisions. Data collection involved distributing questionnaires to 90 respondents, analyzed through multiple linear regression analysis. Results indicate that service quality significantly impacts purchasing decisions, suggesting improved service quality leads to increased purchases at CV. Bali Stars Promosindo. Similarly, product quality positively affects decisions, indicating higher product quality correlates with increased purchases. Enhanced customer experience also positively influences purchasingdecisions, suggesting improved experiences lead to increased purchases. Respondents recommend focusing on timely serviceand enhancing employee product knowledge. Future research should explore meeting and surpassing customer expectations for product quality and ensuring defect-free products for improved customer experience. Emphasizing employee responsiveness through training and strategic exploration can further boost purchasing decisions.